Open Innovation And Digital Marketing: A Catalyst For Culinary SMEs In Makassar - Johannes Baptista Halik; Maria Yessica Halik (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2024)
Through an open innovation process, this study aims to determine the impact of IT awareness and digital marketing on the performance of SMEs in Makassar City. A sample of 94 SMEs using the Lameshow formula was collected in Makassar City for this study. The study shows that in Makassar City, IT awareness and digital marketing have a substantial and beneficial impact on the openness of innovation processes for SMEs. Given the results of this study, it was found that SMEs in Makassar City should start to increase their information technology awareness and use Digital Marketing for Open Innovation processes to improve their performance.